2018
DOI: 10.1097/md.0000000000010639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slow breathing rate on heart rate variability and arterial baroreflex sensitivity in essential hypertension

Abstract: This study is to investigate the effects of slow breathing on heart rate variability (HRV) and arterial baroreflex sensitivity in essential hypertension.We studied 60 patients with essential hypertension and 60 healthy controls. All subjects underwent controlled breathing at 8 and 16 breaths per minute. Electrocardiogram, respiratory, and blood pressure signals were recorded simultaneously. We studied effects of slow breathing on heart rate, blood pressure and respiratory peak, high-frequency (HF) power, low-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 24 publications
7
56
1
3
Order By: Relevance
“…Furthermore, mechanical factors that occur during respiration (stretch of the atria that results from changes in thoracic pressure and cardiac filling) influence HRV independent of changes in cardiac autonomic nerve activity (Billman, 2013b). Several studies have shown that slow, paced breathing strengthens vagal activity and modifies HRV (Howorka et al, 2013;Prinsloo et al, 2013;Kromenacker et al, 2018;Li et al, 2018). In the current study, the influence of breathing on the HRV indices was taken into account by adjusting the results for breathing frequency.…”
mentioning
confidence: 97%
“…Furthermore, mechanical factors that occur during respiration (stretch of the atria that results from changes in thoracic pressure and cardiac filling) influence HRV independent of changes in cardiac autonomic nerve activity (Billman, 2013b). Several studies have shown that slow, paced breathing strengthens vagal activity and modifies HRV (Howorka et al, 2013;Prinsloo et al, 2013;Kromenacker et al, 2018;Li et al, 2018). In the current study, the influence of breathing on the HRV indices was taken into account by adjusting the results for breathing frequency.…”
mentioning
confidence: 97%
“…Previous studies have demonstrated that diabetes is associated with suppressed autonomic activities and blunted baroreflex [19,39]. Previous studies have demonstrated the use of frequency domain [17][18][19] and time domain [20,23] parameters in noninvasively assessing autonomic nervous function in diabetic patients but their sensitivities remain unclear. Taking into account the fact that baroreflex sensitivity is an indicator of autonomic function [15] as well as previous findings showing a good correlation between DVP signals and real-time changes in blood pressure [26][27][28], the current study investigated the possibility of assessing autonomic sensitivity through quantifying the matches between the two time series of DVP and RRI with a shift number of 1 to 5 based on the finding of a previous report that showed a delay of BRS between one to five heartbeats [16].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, frequency domain analysis of heart rate variability (HRV) based on R-R intervals (RRI) from electrocardiograph (EKG) is an assessment method for autonomic nervous activity and baroreflex sensitivity [14]. The parameter of low-to highfrequency power ratio (LFP/HFP, LHR) thus obtained is considered to reflect the relative activities of the sympathetic and parasympathetic nervous systems [17][18][19]. However, such a frequency domain parameter has its limitations because of the nonstationary and nonlinear nature of the physiological signals to be analyzed [20][21][22].…”
Section: Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…SBE has important role on autonomic balance by increasing parasympathetic activity and decreasing sympathetic activity 18 . This exercise improves CANF by increasing parasympathetic activity or decreasing sympathetic activity in some diseases and also in normal healthy person [19][20] .Though several studies investigated effect of SBE on autonomic function in other diseases but there is no published report investigating the effect of SBE on nonlinear measures of HRV in TDT patients. Therefore this study aimed to evaluate the effect of SBE on nonlinear measures(poincaré plot) of HRV in TDT patients so that SBE can be used as an adjunct to conventional treatment and improve CANF as well as reduce the risk of cardiovascular complications.…”
mentioning
confidence: 99%